Lactoferrin as a New Alternative for Prevention of Recurrent Preterm Delivery: A Case Report - Manila Reddy; Manjusha Agrawal; Deepika Dewani; Nidhi Goyal; Dhruva Halani (Journal of Clinical and Diagnostic Research, 2023)
The upper female genital tract connects to the external world through the vaginal canal and can be a potential route of entry to pathogens into the reproductive organs. Lactobacilli exert their protective action by reducing the vaginal pH by producing lactic acid by degrading glycogen released by epithelial cells. Whenever a breach in this intricate defence mechanism or its balance is disturbed, the female genital tract becomes vulnerable to infections. A 30-year-old reported with complaints of abdominal pain and vaginal discharge with poor obstetrical history and had three consecutive Preterm Premature Rupture of Membranes (PPROM) at the 20th, 22nd, and 25th week of gestation. All three pregnancies were natural conceptions. Three consecutive miscarriages were presumed to be due to recurrent vaginitis, cervical inflammation, and chorioamnionitis. The vaginal discharge culture examination was negative for Lactobacilli and positive for gram-positive bacteria. The patient was advised topical antibiotics, oral probiotics containing Lactobacilli species, and prebiotic Lactoferrin 100mg. In a few weeks, Lactobacillus predominant vaginal flora was observed. During pregnancy, she used Lactoferrin and Lactobacillus combination orally until delivery. Cervical maturation was not observed before the term in this gestation. Lactobacillus had been the dominant vaginal flora during pregnancy, and the course of the pregnancy was good. She delivered vaginally at term a healthy male infant. Aetiopathogenesis of preterm delivery in humans has been hypothesised to be triggered by the inflammatory response caused by intrauterine infections. Lactoferrin inhibits the production of inflammatory cytokines and significantly prevents preterm delivery induced by infection.